Adaptation of Community Radio in the New Media Age - Sjuchro, Dian Wardiana; Prasetya, Tri Budi; Rintyarna, Bagus Setya; Prasastiningtyas, Widyapuri; Rezeki, Syailendra Reza Irwansyah (GoAcademica Research & Publishing, 2024)
Community Radio has played an important role in shaping good local governance, village governance, supporting the people's economy, and preserving local wisdom. However, in the current era of new media, the existence of community radio is increasingly tested by various challenges. This study aims to understand how community radio managers adapt to the development of information and communication technology that continues to evolve. The research method used is descriptive with qualitative approach. Community radio is faced with the fact that information and communication technologies are constantly evolving, forming what we know as new media. In earlier eras, radio was identified with a physical device called a radio, but now radio broadcasts can be accessed via online channels or by streaming without being constrained by frequency range. These new media-based broadcasts often lack personal interaction with their listeners. Therefore, to build a more emotional connection with its audience, community radio managers and broadcasters need to adopt a more humanist approach. They seek to strengthen the bond between community radio and its listeners through more direct, responsive, and personalized interactions. Thus, they create stronger bonds and build loyalty among their listeners. This study is expected to provide a deeper insight into the adaptation strategies undertaken by community radio in the face of rapid changes in the media environment. With a better understanding of the challenges and opportunities at hand, community radio can continue to be a relevant and beneficial means for local communities.